MAKNA SERTA EKSISTENSI KEDAULATAN DALAM HUKUM INTERNASIONAL DI MASA MODEREN - I Dewa Gede Agung Wisnu Saputra (Universitas Pendidikan Ganesha, 2022)
This research was conducted to examine and understand deeply the meaning of the existence of sovereignty in the realm of international law today. The main study material for this research is decisions and facts relevant to international law, which are contained in customary international law, general principles of law, international treaties, conventions, declarations and decisions of international declarations. In writing this research journal to find out about the meaning of international legal sovereignty, the method used in writing is descriptive. Which is based on international legal consensus. This study also examines contemporary state sovereignty and relates to international agreements.